Development and Validation of a Stability-Indicating Reversed-Phase High-Performance Liquid Chromatography Method for Assay of Doramectin and Estimation of its Related Substances in Commercial Batches of Doramectin Drug Substance. (21st April 2021) - Wang, Lin; Wimalasinghe, Rasangi; Padivitage, Nilusha; Rustum, Abu M
Abstract: Background: Doramectin is a broad-spectrum antiparasitic drug used in veterinary medicine. It belongs to the family of avermectins, which possess a macrocyclic lactone structure, and is widely used for the treatment of parasites. Objective: This study aimed to develop a stability-indicating reversed-phase (RP) HPLC method for the assay and identification of doramectin including identification and estimation of its related substances in commercial batches of doramectin drug substance. Method: Methanol was used to dissolve and prepare doramectin samples. Doramectin and its related substances were separated on a HALO C8 (100 mm × 4.6 mm i.d., 2.7 µm particle size) column maintained at 40 °C using an isocratic HPLC method with a mobile phase composed of acetonitrile–water (70 + 30, v/v). Analytes were detected with UV detection at 245 nm and quantitated against a single point external reference standard of doramectin. The LOQ of the method is 0.1% of the target concentration as described in the method. Results: The HPLC method can separate all analytes of interest by an isocratic elution within 10 min. The method was validated according to the guidelines described in the International Conference on Harmonization Q2(R1). Conclusions: The HPLC method for assay of doramectin and estimation of its related substances was successfully developed, validated, and demonstrated to be accurate, robust, specific, and stability-indicating. Highlights: This is the first known paper to report an HPLC method for assay of doramectin and estimation of its related substances in commercial batches of doramectin drug substance.